GIANT CUBITAL FOSSA LIPOMA MIMICKING HAEMATOMA FOLLOWING VASCULAR ACCESS: A CASE REPORT AND REVIEW OF LITERATURE - Bello US (Ntec Specialist, 2016)
Background: Lipomas are the most common type of mesenchymal tumours, but giant lipomas of the upper extremities are rare. This tumour is slow growing and a rapid growth should herald suspicion of malignancy or a slit in the fascia that abruptly protrude a deep sited lipoma following a trigger. Objectives: To highlight traumatic vascular access precipitating a rapid growing cubital lipoma that mimicked a haematoma and review of existing literature. Methods: Data on clinical, operative and laboratory findings of a 26-year-old female were reviewed and followed, after noticing a progressive swelling subsequent to vascular access. Results: A lipoma measuring 8cm x 5cm x 4cm was excised from the cubital fossa for a rapid growing swelling after eventful vascular access. Conclusion: A rare case of venepuncture as a likely trigger of the giant cubital fossa lipoma and this awaken attention to regular refresher training on vascular access as a recommendation